2019
DOI: 10.1111/nep.13678
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the most clinically useful skeletal muscle mass indices pertinent to sarcopenia and physical performance in chronic kidney disease

Abstract: Aim: Patients with chronic kidney disease (CKD) are characterised by low skeletal muscle mass that negatively impacts physical performance. Operational definitions of 'low muscle mass' are inconsistent, and it is unknown how different skeletal muscle mass indices affect the relationship between muscle mass and physical function.Methods: Appendicular skeletal muscle mass (ASM) was measured by dual-energy X-ray absorptiometry in 72 CKD patients. Along with crude ASM, alternative muscle indices were calculated ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Our study showed that the proportion of individuals of sarcopenia was high and consistent with those reported in some previous studies. For instance, Thomas et al found a 19% prevalence of sarcopenia in a research involving British non-dialysis adults [19]. In Dutch patients, the prevalence of sarcopenia was 23.3% [20].…”
Section: Discussionmentioning
confidence: 98%
“…Our study showed that the proportion of individuals of sarcopenia was high and consistent with those reported in some previous studies. For instance, Thomas et al found a 19% prevalence of sarcopenia in a research involving British non-dialysis adults [19]. In Dutch patients, the prevalence of sarcopenia was 23.3% [20].…”
Section: Discussionmentioning
confidence: 98%
“…Physical function and strength were assessed using frequently used assessments previously described in Wilkinson et al 1 Handgrip strength (HGS) of the dominant and non-dominant hands were assessed using a JAMAR hydraulic handheld dynamometer (Fabrication Enterprises Inc, Irvington, New York). Each participant had three attempts with each hand and the maximal score was taken for both.…”
Section: Methodsmentioning
confidence: 99%
“…Skeletal muscle health decreases with advancing age and several disease states, including chronic kidney disease (CKD). 1 , 2 This loss of skeletal muscle mass contributes to impairments in strength and physical function; 3 however, these adverse changes cannot be entirely accounted for by changes in muscle size. The concept of muscle quality is increasingly being used to assess skeletal muscle health.…”
Section: Introductionmentioning
confidence: 99%
“…Described as a having model of “accelerated aging,” patients with chronic kidney disease (CKD) have aberrant changes in body composition, including wasting of skeletal muscle 1–5 . These changes are associated with increased mortality and adverse clinical outcomes 6,7 .…”
mentioning
confidence: 99%
“…Numerous factors are involved in these changes, including malnutrition, inflammation, and physical inactivity 1,8 . Prevalent in around one‐third of patients with CKD, 4,6 the term “sarcopenia” is hallmarked by the presence of low muscle mass 9 . Although tools such as bioelectrical impedance analysis (BIA), magnetic resonance imaging, dual‐energy x‐ray absorptiometry (DXA), and computed tomography are suggested by the European Working Group for Sarcopenia in Older People, access to these techniques may be limited by a lack of facilities, technical expertise, cost, and methodological concerns (eg, exposure to radiation) 10 .…”
mentioning
confidence: 99%